Interfacial activity and emulsifying behaviour of inclusion complexes between helical polysaccharides and flavouring molecules resulting from non-covalent interactions. (March 2018) - De Fenoyl, Louise; Hirel, Déborah; Perez, Emile; Lecomte, Sophie; Morvan, Estelle; Delample, Mathieu
Abstract: This study deals with the fabrication of inclusion complexes starting from a cross coupling of seven helical polysaccharides (host) and six flavouring agents (guest). Neither of the substrates is considered as an emulsifier when studied alone. Due to a complexation mechanism, the presence of intermolecular hydrogen bonds between substrates was highlighted by infra-red spectroscopy and 13 C NMR. In addition, depending on the polysaccharide used, the guest molecule could be preferentially located either inside or in the interstitial spaces of the helix. In a comparison between raw substrates, the inclusion complexes obtained presented the unique interfacial activity of decreasing surface tension values (γ) and, in some cases, their behaviour in water was similar to that of regular emulsifiers due to the presence of a critical aggregation concentration (CAC). Substrate concentrations and the ratios between them were the main parameters investigated in this study, which focused on the two inclusion complexes: vanillin/amylose and vanillin/ι-carrageenan. The first decreased γ values by as much as 53 mN/m with a double transition, whereas the second could cause γ fall to 36 mN/m with a regular break. In addition, these systems were able to stabilize foams for up to 60 min, which confirmed their unique emulsifying properties. Graphical abstract: Highlights: Flavouring molecules form inclusion complexes with helical polysaccharides. Inclusion complexes present the ability to decrease surface tension. Ratios between raw substrates impact the surface tension. Vanillin is located either inside polysaccharide helix or in its interstitial spaces. Best associations are able to stabilize foams for up to 60 min.